MEMERIKSA TPACK GURU SMP NEGERI DAN BERPENGALAMAN DAN PENGARUHNYA TERHADAP PENGEMBANGAN PROFESIONAL - Sumarsono, Anne Yustica Pramesti (Perspektif Ilmu Pendidikan, 2022)
Abstract: The use of technology in education is highly significant nowadays. Currently, blended learning is used in Indonesia, which requires students and teachers to communicate via social media. Students from SMP Karanglewas, enter school in turn according to the schedule, and when students study at home, the teacher must deliver materials or tasks through social media. The researcher would learn about the novice and experienced teachers' perceptions of TPACK, as well as the activities that teachers took based on their usage of technology. There were two study questions: What are novice and experienced teachers’ perceptions of TPACK? and To what extent have their actions been inspired by TPACK? The objectives were to investigate beginner and experienced SMP Karanglewas instructors' variations in their TPACK, as well as to learn about the influences on professional development and the behaviours inspired by TPACK. The findings where teachers could apply TPACK well even though they need help from other people and the difference between novice and experienced teachers in terms of technology was different because novice teachers had high technology knowledge but experienced teachers, were good at pedagogy content knowledge. Keywords: TPACK; professional development; novice teachers; experienced teachers; the influence of TPACK